‘Echoes from Home’: The Personalist Ground of Newman’s Ecclesiology. Affection as the Key to Newman’s Intellectual Discernment on the Issue of Church - Dr Robert C. Christie (Cahiers Victoriens et Edouardiens)
Newman’s majestic work, An Essay on the Development of Christian Doctrine (October, 1845), explicated a logical argument for the Roman communion as the rightful heir of the Apostolic church, culminating in an ecclesiastical odyssey that began almost thirty years earlier in his religious conversion of 1816. I suggest that in addition to the intellectual import of the Essay, at least of equal significance is the principle underlying Newman’s analysis, which is that intellectual discernment through affection is the ground of faith. For more than two decades, Newman’s journey traveled along these two parallel tracks—that of religious epistemology grounded in the affections, and that of ecclesiastical discernment—ultimately arriving ‘home’ in the Roman Catholic Church. The groundwork for the Essay was laid in Newman’s final University Sermon written almost two years earlier (February 2, 1843). Here we discover a major clue in a metaphor Newman used to describe his sense of dogma: ‘They are the echoes from our Home.’